1989
DOI: 10.1021/j100351a036
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of alkyl peroxynitrates

Abstract: X 1027 exp(-10766 K/F) molecule cm"3 is obtained for the equilibrium CH300N02 " CH300 + N02. Some experiments were performed on the thermal decomposition of isomeric mixtures of butyl, hexyl, and octyl peroxynitrate at 253 K and in 800 mbar of N2. Atmospheric implications of the thermal stability of alkyl peroxynitrates are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 0 publications
3
72
0
4
Order By: Relevance
“…Plot of the experimental versus the MESMER calculated values for k -1 . The high values are from this study ( ) and Bridier et al 5 ( ) and the low values ( ) are from the nitrate decomposition studies of Zabel et al 7 The slope is equal to 1.007 ± 0.012, which indicates exceptional agreement. are in excellent agreement as shown in Figure 5, which is a correlation plot for the experimental and calculated rate constants.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Plot of the experimental versus the MESMER calculated values for k -1 . The high values are from this study ( ) and Bridier et al 5 ( ) and the low values ( ) are from the nitrate decomposition studies of Zabel et al 7 The slope is equal to 1.007 ± 0.012, which indicates exceptional agreement. are in excellent agreement as shown in Figure 5, which is a correlation plot for the experimental and calculated rate constants.…”
Section: Resultssupporting
confidence: 57%
“…More recently Jimenez et al 24 measured both  OH,PNA (0.09) and  HO2,PNA (0.89), which questioned the validity of the measurements of Macleod et al 22 1-,2-C 4 H 9 O 2 + NO 2 1-,2-C 4 H 9 O 2 NO 2 (3) , (-3) No studies have been carried out into the kinetics of the forward reaction, but measurements have been made for (CH 3 ) 3 CO 2 . 25 As with the other RO 2 NO 2 molecules in this study Zabel et al 7 has measured its decomposition kinetics.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Figure 3 shows the results of simulations for atmospheric trace species that yield NO 2 upon thermal dissociation under these conditions, with pressure reduction at point B. Rate constants were added for ClNO 2 (Baulch, et al, 1981;Knauth and Martin, 1978), BrONO 2 (Orlando & Tyndall, 1996), ClONO 2 (Anderson & Fahey, 1990), and CH 3 OONO 2 (Zabel, et al, 1989). The dissociation temperatures of these species have not been experimentally verified for this instrument, but it has been reported that nitryl chloride (ClNO 2 ) requires a higher temperature for dissociation than that normally used for measurement of PANs (Osthoff, et al, 2008).…”
Section: Instrument Construction and Operationmentioning
confidence: 99%